Acute toxicity of normofractionated intensity modulated radiotherapy with simultaneous integrated boost compared to three-dimensional conformal radiotherapy with sequential boost in the adjuvant treatment of breast cancer - Krug, David; Köder, Christine; Häfner, Matthias; Arians, Nathalie; Harrabi, Semi B.; Körber, Stefan A.; Forster, Tobias; Schlampp, Ingmar; Sohn, Christof; Heil, Jörg; Hof, Holger; Hörner-Rieber, Juliane; et al. (Radiation oncology, 2020)
Intensity-modulated radiotherapy (IMRT) improves dose homogeneity and late toxicity compared to simple tangential techniques in adjuvant whole-breast radiotherapy for patients with breast cancer. Simultaneous-integrated boost (SIB) radiotherapy shortens the overall treatment time and improves dose homogeneity. However, prospective randomized trials regarding IMRT with SIB for adjuvant radiotherapy in breast cancer are lacking.
Gesehen am 03.12.2020